Structure, function, aging and turnover of aggrecan in the intervertebral disc - Sivan, Sarit Sara; Wachtel, Ellen; Roughley, Peter (Biochimica et biophysica acta, 2014)
Aggrecan is the major non-collagenous component of the intervertebral disc. It is a large proteoglycan possessing numerous glycosaminoglycan chains and the ability to form aggregates in association with hyaluronan. Its abundance and unique molecular features provide the disc with its osmotic properties and ability to withstand compressive loads. Degradation and loss of aggrecan result in impairment of disc function and the onset of degeneration. This review summarizes current knowledge concerning the structure and function of aggrecan in the normal intervertebral disc and how and why these change in aging and degenerative disc disease. It also outlines how supplementation with aggrecan or a biomimetic may be of therapeutic value in treating the degenerate disc. Aggrecan abundance reaches a plateau in the early twenties, declining thereafter due to proteolysis, mainly by matrix metalloproteinases and aggrecanases, though degradation of hyaluronan and non-enzymic glycation may also participate. Aggrecan loss is an early event in disc degeneration, although it is a lengthy process as degradation products may accumulate in the disc for decades. The low turnover rate of the remaining aggrecan is an additional contributing factor, preventing protein renewal. It may be possible to retard the degenerative process by restoring the aggrecan content of the disc, or by supplementing with a bioimimetic possessing similar osmotic properties. This review provides a basis for scientists and clinicians to understand and appreciate the central role of aggrecan in the function, degeneration and repair of the intervertebral disc. •Aggrecan abundance reaches a plateau in the early twenties, then slowly declines.•Aggrecan abundance declines due to proteolysis, mainly by MMPs and aggrecanases.•Aggrecan loss is an early event in disc degeneration.•The low turnover rate of the degraded aggrecan prevents its replacement.•Aggrecan restoration or bioimimetic supplementation may retard disc degeneration.